Prevalence of noncommunicable diseases and usage of healthcare devices among the masses dwelling in South India, Kadapa - Poornachand Tadisetti, Hari Kumar Cheedella, Ranakishor Pelluri (Journal of Applied Pharmaceutical Science, 2022)
Noncommunicable diseases (NCDs) are much prevalent nowadays and majority of the patients utilize different medical devices in order to manage these diseases. Hence, there is a strong need to evaluate the utility of medical devices by the population of these diseases. The current study aimed to assess the usage of medical devices for disease management in the urban and rural settings of a south Indian district. A cross-sectional study was carried out for 18 months with the subjects who met the inclusion criteria. The subjects were recruited into the study by obtaining the ethics committee approval and informed consent from all subjects. A total of 3,000 subjects were screened and among them 1,024 (34.13%) subjects were recruited, with 593 (57.91%) subjects belonging to rural settings and 431 (42.08%) subjects belonging to urban settings. 559 were male (54.68%) and 464 were female (45.31%). In the subjects selected, patients with diabetes and hypertension covered the major part, with 70.70% among other NCDs. Medical devices usage awareness was observed among 520 (50.78%) subjects of the total recruited subjects, and among them 327 (68.65%) and 193 (37.11%) subjects were urban and rural areas, respectively. Some of the commonly used devices among the subjects were glucometers, digital BP apparatus, thermometer, pulse oximeter, and inhaler machine, which constituted about 186 (35.96%), 82 (15.76%), 181 (34.42%), 24 (4.80%), and 47 (9.03%), respectively. Overall, the awareness of medical device usage among the total subjects recruited was found to be 50.78%, with a slightly higher percentage of awareness in urban areas (62.88%; n = 327) as compared to rural settings (37.11%; n = 193). Hence, it is essential to see that both the rural and urban areas’ population need greater awareness on utilization of medical devices through different initiatives.
Keywords: Disease management, medical device, noncommunicable diseases, South India